The Influence of Financing Risk on Mudharabah Financing in Islamic Commercial Banks - Endra Herdiansyah; Fadhila Nurul Azqia; Annisa Adha Minaryanti; Budi Septiawan (CV Edujavare Publishing, 2026)
The Influence of Financing Risk on Mudharabah Financing in Islamic Commercial Banks